Gnathostomiasis acquired after consumption of raw freshwater fish in the Amazon region: a report of two cases in Brazil - Haddad Junior, Vidal [UNESP]; Oliveira, Isis Fiorello de [UNESP]; Bicudo, Natalia Parenti [UNESP]; Alencar Marques, Mariangela Esther [UNESP] (Soc Brasileira Medicina Tropical, 2021)
Gnathostomiasis is a parasitic zoonosis caused by the helminth Gnathostoma spp., acquired through the consumption of raw or undercooked contaminated aquatic animals:The disease is endemic in Southeast Asia and Central America. Two male patients, both middle-aged, presented with single itchy erythemato-edematous plaques on the anterior thorax and left flank. Both had consumed raw fish in the Amazon region. The clinical and epidemiological examinations suggested gnathostomiasis, and treatment with albendazolc caused total regression of the lesions. Health teams should be familiar with the disease to provide correct diagnosis. The control strategy should be based on health education for the population.
Keywords: Gnasthotomiasis; Worm infestations; Fish; Peacock bass